DIRECTIONS OF DEVELOPMENT OF UNIVERSAL HUMAN RIGHT TO A HEALTHY ENVIRONMENT - Nikolic, Dusan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The process of political shaping of the right to a healthy environment, started with the adoption of the Stockholm Declaration in 1972, basically ended only fifty years later, when the United Nations Assembly adopted the Resolution declaring access to a clean, healthy and sustainable environment as a universal human right. At the beginning of the long journey, the responsibilities for implementing the decisions expressed in the Stockholm Declaration were divided between the member states, on the one hand, and the international community, on the other.The dominant position was given to state authorities. It was agreed that they must be entrusted with the task of planning, managing and controlling ecological resources, in order to improve the quality of the environment, and that states have the right to sovereignly exploit their own resources in accordance with their environmental protection policy. On the other hand, the belief was expressed that the international community will find a source of strength for later concrete action in the Stockholm Declaration. Since then, very modest progress has been made at international level.Official UN statements noted that the 2022 Resolution is not legally binding for 193 member states, but that its proponents hope it will encourage countries to enshrine the right to a healthy environment in national constitutions and regional treaties and encourage them to implement laws that relate to that right, and that it will help people fight for their right to a safe climate, their right to breathe clean air and their rights to access clean and safe water, adequate food, healthy ecosystems and a non-toxic environment. In the global context, the right to a healthy environment is still aspirational (imperfect, unfinished), something that still needs to be fought for at the national level. It will remain so until the consumer society model is replaced by a new form of social organization, which will be based on a different value system. Such a conclusion is also indicated by the reasonable, well-balanced judgement of the Court of Justice of the European Union at the end of 2022, in the case of JP v. Ministre de la Transition écologique (C-61/21). It stated that the provisions of the directives related to air quality must be interpreted in the sense that they do not aim to give individuals the right to seek compensation from the member state for loss and damage caused by the state's violation of EU law, but that it does not excludes the possibility of an individual claiming compensation from the state on the basis of national law.During the past half century, about 150 countries around the world have constitutionalized the right to a healthy environment. It thus, at the national level, gained a significantly different physiognomy and more effective protection not only before the courts of general jurisdiction, but also before the constitutional courts, in proceedings regarding constitutional appeals. However, some new problems arise here. Among them, the competition (conflict) of property rights and certain sectoral rights included (integrated) within universal human right to a healthy environment, such as the right to water, which is discussed in this paper, is particularly significant. In conditions where it is not possible to satisfy the interests of everyone, states will be forced to prioritize their own citizens, and that means civil (private) rights, over universal human rights for the sake of social stability and the preservation of internal order. The process of constitutionalization will be slowed down, and it is possible that in some countries a kind of deconstitutionalization will be carried out, by amending the constitution or informally, through a more restrictive application of universal human rights and more restrictive decision-making regarding constitutional appeals.In the final part of the paper, it was stated that the boundaries between traditional subjects and objects of law are gradually being erased and that the environment must eventually be understood as a community of all living beings, which has a specific legal subjectivity and the right to be healthy.